Reconstructing The Nature Of Inclusive School System In Primary School To Strengthening Inclusive Society - Zidniyati Zidniyati (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
This paper contains theoretical discussions about the nature of inclusive education and the implications needed in the practice of inclusive school systems, especially at the elementary school level. The formulation of the problem raised in this study is: What is the nature of the implementation of the inclusive education system in elementary schools? What are some examples of inclusive education practices so far? What is the relationship between inclusive education and value education in schools? How can inclusive education strengthen inclusive communities? What are the implications of implementing the inclusive education system in elementary schools? The five questions will be answered by a discussion approach on various theories that have been raised by many experts and by looking at the practices of inclusive education in several developing countries and developing countries. This research used literature review methods. The findings in this study are that inclusive education will be realized in an inclusive community environment that holds fast to the values of mutual acceptance, mutual respect, and mutual love for one another. In other words, inclusive education means preparing all members of the inclusive community in schools for inclusive communities.